Implementasi Smart Home Pada Pendeteksi Dini Kebakaran Menggunakan Forward Chaining - Wahyono, Irawan Dwi; Priyantono, Mochammad Bagus (Universitas Andalas, 2020)
Fire is a disaster that can occur due to human negligence. So we need a system that functions to minimize the occurrence of fires by having a working concept to detect fires. This study aims to develop a fire detection system using the forward chaining method. In this detection system applying Artificial Intelligence where there are parameters of temperature, gas, the presence of fire, and the presence of water. This system also applies the Smart Home concept to detect fires early where there are sensor devices used by DHT 11, FLAME and MQ2. the data obtained from the sensor will be processed by the NodemCU Esp-8266 microcontroller. If there is an indication that caused a fire, the system immediately sends a warning via telegram. The results of this study obtained a precision of .94%, recall 93.6% and an accuracy of 96%.